Proteomic identification of phosphatidylinositol (3,4,5) triphosphate-binding proteins in Dictyostelium discoideum - Zhang, Pingbo (National Academy of Sciences, 2010)
Phosphatidylinositol (3,4,5)-triphosphate (PtdInsP(3)) mediates intracellular signaling for directional sensing and pseudopod extension at the leading edge of migrating cells during chemotaxis. How this PtdInsP(3) signal is translated into remodeling of the actin cytoskeleton is poorly understood. Here, using a proteomics approach, we identified multiple PtdInsP(3)-binding proteins in Dictyostelium discoideum, including five pleckstrin homology (PH) domain-containing proteins. Two of these, the serine/threonine kinase Akt/protein kinase B and the PH domain-containing protein PhdA, were previously characterized as PtdInsP(3)-binding proteins. In addition, PhdB, PhdG, and PhdI were identified as previously undescribed PH domain-containing proteins. Specific PtdInsP(3) interactions with PhdB, PhdG, and PhdI were confirmed using an in vitro lipid-binding assay. In cells, PhdI associated with the plasma membrane in a manner dependent on both the PH domain and PtdInsP(3). Consistent with this finding, PhdI located to the leading edge in migrating cells. In contrast, PhdG was found in the cytosol in WT cells. However, when PtdInsP(3) was overproduced in pten(−) cells, PhdG located to the plasma membrane, suggesting its weak affinity for PtdInsP(3). PhdB was found to bind to the plasma membrane via both PtdInsP(3)-dependent and -independent mechanisms. The PtdInsP(3)-independent interaction was mediated by the middle domain, independent of the PH domain. In migrating cells, the majority of PhdB was found at the lagging edge. Finally, we deleted the genes encoding PhdB and PhdG and demonstrated that both proteins are required for efficient chemotaxis. Thus, this study advances our understanding of the PtdInsP(3)-mediated signaling mechanisms that control directed cell migration in chemotaxis.